(untitled) (World Economics and Finance Bulletin, 2022)
The purpose this study to measure and analyze the impact of the relationship between indicators of financial engineering innovations in reducing financial distress and improving performance for a sample of companies listed on the Iraqi Stock Exchange, The research community represented in the industrial sector for companies listed in the Iraq Stock Exchange for a period of three years and for the period extending from (2019-2021), The researchers reached a number of conclusions, the most important of which are(Reliance on financial engineering indicators leads to a decrease in the occurrence of financial stumbling, as the increase in dependence on financial engineering indicators by one unit leads to a decrease in financial stumbling by (1.430) referred to by a coefficient (B). The researchers reached a number of recommendations, the most important of which are(We recommend the Iraqi Company for Engineering Works and the Iraqi Company for Carpets and Furniture to overcome the critical situation it is exposed to as a result of financial stumbling through developing performance and improving the quality of goods and services to gain customer satisfaction).